Heavy : an American memoir [compact disc, unabridged] - Laymon, Kiese (Simon & Schuster Audio, 2018)
In this powerful and provocative memoir, genre-bending essayist and novelist Kiese Laymon explores what the weight of a lifetime of secrets, lies, and deception does to a black body, a black family, and a nation teetering on the brink of moral collapse.